Anisotropy of the non-equilibrium quasiparticle dynamics in single crystals of YBa2Cu3O7-delta - Stevens, C; Gay, P; Smith, D; Chen, C; Ryan, J (1999)
We report for the first time, measurements of ultrafast transients from YBCO in which the contributions from a- and b-axis response are separately identified using polarised light. A new signal is observed for E parallel to a which has been obscured in all previous thin film experiments. Comparing the two contributions we find the new signal to be sensitive to T-c whilst the signal for E parallel to b exhibits pseudogap behaviour.